2008
DOI: 10.1002/iub.41
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and rheumatoid arthritis

Abstract: SummaryVitamin K2 [menaquinone-4 (MK-4)] has been reported to induce apoptosis in hepatocellular carcinoma, leukemia, and MDS cell lines. The effects of MK-4 on the development of arthritis have never been addressed so far. In this study, we investigated the effect of MK-4 upon the proliferation of rheumatoid synovial cells and the development of arthritis in collageninduced arthritis (CIA). We analyzed the effect of MK-4 on the proliferation of fibroblast-like synoviocytes (FLSs) using the 3-(4,5-demethylthia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
(37 reference statements)
0
16
0
1
Order By: Relevance
“…Our data are consistent with these observations and suggest that vitamin K2-mediated down-regulation of inflammation may also translate into reduced RANKL production by immune and other cells, thus amplifying the direct suppressive effects of this agent on osteoclastogenesis and bone resorption through inhibitory effects on NF-κB activation. In fact vitamin K2 is reported to mediate potent anti-inflammatory effects on arthritis in vivo and to suppress the development of arthritis in the collagen-induced arthritis (CIA) animal model (49). The importance of the NF-κB pathway in the development of rheumatoid arthritis is well established and the pharmacological suppression of NF-κB activation itself is reported to ameliorate bone erosions in a rheumatoid arthritis animal model in vivo (9).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with these observations and suggest that vitamin K2-mediated down-regulation of inflammation may also translate into reduced RANKL production by immune and other cells, thus amplifying the direct suppressive effects of this agent on osteoclastogenesis and bone resorption through inhibitory effects on NF-κB activation. In fact vitamin K2 is reported to mediate potent anti-inflammatory effects on arthritis in vivo and to suppress the development of arthritis in the collagen-induced arthritis (CIA) animal model (49). The importance of the NF-κB pathway in the development of rheumatoid arthritis is well established and the pharmacological suppression of NF-κB activation itself is reported to ameliorate bone erosions in a rheumatoid arthritis animal model in vivo (9).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that MK-4 could induce apoptosis of synovial cells and thus be a novel treatment for RA [17][18]. Therefore, it is necessary to study the correlation between circulating vitamin K homologues levels in RA patients and RA biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…We consider that the use of vitamin K1 oxide in cosmetics may lead to unnecessary sensitization in patients, who may then be denied vitamin K‐containing therapies for treatment of important systemic diseases. Vitamin K is widely used in medicine and new significance therapeutic indications are being studied (17–19).…”
Section: Discussionmentioning
confidence: 99%